Forming and actualization of cognitive motives as means for development of students' analytical thinking. - Shevchenko Svetlana Nikolaevna (Kharkov National Pedagogical University, 2011)
Considered different approaches to understanding the concepts of motivation and motive. Species analyzed motives of educational activity. Established that cognitive motives are most effective for the development of analytical thinking of students. The study used data from test 1-4 grade students. An interconnection between the level of academic achievement and student motivation level of its training. Isolated areas of forming and maintaining cognitive motives of students in the learning process. It is established that the formation and activation of the cognitive motivation of students affected: the content of educational material, organizing training activities, style of teaching. Each component provides the motivational aspect of students to study.